Experimentally manipulating light spectra reveals the importance of dark corridors for commuting bats. (26th October 2018) - Zeale, Matt R. K.; Stone, Emma L.; Zeale, Emma; Browne, William J.; Harris, Stephen; Jones, Gareth
Abstract: The rapid global spread of artificial light at night is causing unprecedented disruption to ecosystems. In otherwise dark environments, street lights restrict the use of major flight routes by some bats, including the threatened lesser horseshoe bat Rhinolophus hipposideros, and may disrupt foraging. Using radio tracking, we examined the response of individual female R. hipposideros to experimental street lights placed on hedgerows used as major flight routes. Hedgerows were illuminated on one side over four nights using lights with different emission spectra, while the opposite side of the hedge was not illuminated. Automated bat detectors were used to examine changes in overall bat activity by R. hipposideros and other bat species present. R. hipposideros activity reduced significantly under all light types, including red light, challenging a previously held assumption that red light is safe for bats. Despite this, R. hipposideros rapidly adapted to the presence of lights by switching their flight paths to the dark side of the hedgerow, enabling them to reach foraging sites without restriction. Red light had no effect on the activity of the other species present. Slow‐flying Myotis spp. avoided orange, white and green light, while more agile Pipistrellus spp. were significantly more active at these light types compared to dark controls, most probably in response to accumulations of insect prey. No effect of any light type was found for Nyctalus or Eptesicus spp. Our findings demonstrate that caution must be used when promoting forms of lighting that are thought to be safe for wildlife before they are tested more widely. We argue that it is essential to preserve dark corridors to mitigate the impacts of artificial light at night on bat activity and movements. Abstract : Using field experiments, we investigated the responses of bats to street lights with different emission spectra. Fast‐flying species are attracted to orange, white and green light, while slower‐flying species are deterred. The threatened lesser horseshoe bat Rhinolophus hipposideros is also deterred by red light, challenging a previously held assumption that red light is safe for bats. Using radio tracking, we demonstrate that the impact of lights on R. hipposideros can be mitigated by controlling light spill along preferred commuting routes. We argue it is essential to preserve dark corridors to mitigate the impacts of light pollution on bats.